KEANEKARAGAMAN JENIS DAN KELIMPAHAN POPULASI SERANGGA AIR SEBAGAI INDIKATOR BIOLOGIS CEMARAN AIR PADA DAS DI LANGOWAN - Maramis, Redsway T.D.; Makal, Henny V.G. (EUGENIA, 2011)
ABSTRACT Â  Aquatic insects are one of the organisms that are used in determining water contamination. Aquatic insects are sensitive to the presence of waste dumped in the river and some are resistant to such waste. One of insect resistant waste is Chironomidae. The research objective was to determine aquatic insect species, population abundance by calculating indices diversity and biotic index. Aquatic insects in the lake watershed Tondano were collected by kicks and Hand Picking. Result showed that seven orders, theerteen families and sixteen species had been identified. The number of highest aquatic insect was found in Noogan which were 13 species, whereas in karondoran were 9 species. Aquatic insects were identified including, Heptagenia sp, sp Baetis sp, Caenis sp., Hydropsyhe, sp and Chrironomidae. The highest aquatic insect populations were collected in Karondoran followed by Winebetan and Noogan. The highest diversity index of aquatic insects was found in Winebetan whereas the lowest was in Karondoran. The lowest value of the biotic index was identified in the region Noogan suggested that water in Noogan area was clean water compared to Winebetan and Karondoran. Key word: Types and aquatic insect populations